Inocencio Aguado and Felipe Boero: ¿Why That Other? Controversies about the Himno a Sarmiento. (Revista Argentina de Musicología, 2014)
We discuss the meanings, aesthetic values and the political sense attributed to two hymns to Domingo Faustino Sarmiento created intentionally for the commemorations of the fiftieth anniversary of his death in 1938. Felipe Boero, promoter of musical nationalism, composed the Hymn to Sarmiento based on Eduardo María de Ocampo’s poem commissioned by the National Council of Education. Inocencio Aguado Aguirre set to music Juan Solano Luis’s Hymn to Sarmiento on the fiftieth anniversary of his death, at the request of the General Council of Education of San Juan. We also discuss the omission of the hymn of Ocampo-Boero from the commemorations in San Juan, Sarmiento´s home town, which produced polemics between musicians linked to the national and the provincial governments. The conflict showed the struggles around political issues and cultural hegemony.
Keywords: hymns; Sarmiento; polemics; local history of music